2022
DOI: 10.1155/2022/8065771
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Mesenchymal Stromal Cell-Derived Exosomes Prevent Testicular Torsion Injury via Activating PI3K/AKT and MAPK/ERK1/2 Pathways

Abstract: Adipose mesenchymal stromal cell-derived exosomes (ADSC-Exos) have shown great potential in the treatment of oxidative stress induced by ischemia-reperfusion injury. However, alleviation of testicular torsion injury by ADSC-Exos has not been reported. Therefore, we investigated the protective effect of ADSC-Exos against testicular torsion-detorsion injury. ADSC-Exos were isolated by ultracentrifugation and injected into torsion-detorsion-affected testes of rats. H&E staining and sperm quality were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Exo therapy at a single dose signi cantly improved in tissue repair via regulating Cis-induced autophagy. Previous studies have showed that exos protected against testicular ischemia/reperfusion injury in rats through antioxidant, anti-in ammatory, and antiapoptotic mechanisms (43,44). It has also been reported that antitumoural drugs trigger the autophagy process.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Exo therapy at a single dose signi cantly improved in tissue repair via regulating Cis-induced autophagy. Previous studies have showed that exos protected against testicular ischemia/reperfusion injury in rats through antioxidant, anti-in ammatory, and antiapoptotic mechanisms (43,44). It has also been reported that antitumoural drugs trigger the autophagy process.…”
Section: Discussionmentioning
confidence: 97%
“…(52) Exosomes with antiapoptotic, anticancer, and antioxidant qualities have been reported to lower oxidative stress in the area of damage. (19,44,53,54) The primary functions of the testicles are the production of testosterone and sperm.…”
Section: Discussionmentioning
confidence: 99%
“… 102 However, other researchers found that adipose mesenchymal stem cell-derived exosomes (ADSC-Exos) inhibit inflammatory responses by activating the phosphatidylinositol 3 kinase/protein kinase B (PI3K/AKT) and mitogen-activated protein kinases/extracellular signal-regulated kinases 1/2 (MAPK/ERK1/2) pathways to reduce oxidative stress and promote macrophage polarization toward the M2 phenotype. 103 This reduces the damage of testicular torsion. It also promotes the proliferation and migration of spermatogenic cells and inhibits their apoptosis.…”
Section: The Prospects Of Exosomes In the Treatment Of Male Infertili...mentioning
confidence: 99%
“…Ischemia-reperfusion injury is related to overgeneration of reactive oxygen species [3][4][5]. Increased reactive oxygen species have deleterious effects on cellular components by causing lipid peroxidation, structural alteration of protein, and DNA oxidation [6].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Damage caused by testicular torsiondetorsion is an ischemia-reperfusion injury. In the process of ischemia-reperfusion, excessive reactive oxygen species are formed in tissue [3][4][5]. Reactive oxygen species, like superoxide anions, nitric oxide, hydrogen peroxide, hypochlorous acid, hydroxyl radicals, and singlet oxygen, are highly reactive and can damage cellular constituents, such as lipids, proteins, deoxyribonucleic acid, and carbohydrates, finally leading to the loss of cellular viability and even cellular death [6].…”
Section: Introductionmentioning
confidence: 99%